Unusual Complications after Transcatheter Aortic Valve Replacement: Gastrointestinal Bleeding in an Elderly Patient with Previous Coronary Artery Bypass Graft: A Case Report - Habib Haybar; Ata Firouzi; Mozhdeh Poorkhorshid; Seyed Salaheddin Nabavi; Abazar Parsi; Najmaldin Saki; Seyed Sobhan Bahreiny; Mojtaba Aghaei (Advanced Biomedical Research)
The care of an 89-year-old male patient with severe as who underwent transcatheter aortic valve replacement (TAVR) with the MYVAL 24.5 valve is the subject of this case study. The patient’s medical history was complicated by osteoporosis, advanced age, and a prior coronary artery bypass graft (CABG). Despite a successful TAVR procedure, the patient experienced a series of difficult and uncommon post-operative gastrointestinal bleeds.